PEMBELAJARAN KEBENCANAAN BAGI MASYARAKAT DI DAERAH RAWAN BENCANA BANJIR DAS BERINGIN KOTA SEMARANG (Faculty of Social Science, Universitas Negeri Semarang, 2015)
The high level of flood risk that occurs in Semarang city, raises the level of anxiety in the community , so it needs to have integration in community disaster education . The purpose of this paper is to inform the public profile of the flood prone areas in the form of non-spatial data base ( behavior towards disaster , habits and aspirations of the community in the face of disaster), and a disaster for developing learning models in shaping the character of the community . While the methods used are qualitative and Research and Development ( RnD ) The results showed that there is still a lack of knowledge in the society faces a disaster , it is shown by the lack of social and physical infrastructure of flood disaster . On the other hand to increase the capacity of communities to deal with disasters , disaster on the community learning can be done with the participation of the community ranging from mitigation , preparedness , disaster response , to recovery .Lessons of disaster is one of the strategies in the character building , because learning through disaster also internalized values ? ? of at least three characters , namely social care , care for the environment , and creative . Social care is realized by mutual cooperation , caring environment with hygiene and environmental conservation activities , and creative embodied through effective post-disaster management .